2019
DOI: 10.1088/1361-6420/ab0ccd
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the linear sampling method for time-dependent fields

Abstract: The linear sampling method seeks to localize the unknown source of an observed, time-dependent field. The unknown source could be, for example, a scatterer embedded within a medium, or an impulsive excitation such as an earthquake or explosion. The source of the observed field is localized by means of solving the so-called near-field equation and mapping the obtained solutions through an indicator functional over a test region assumed to contain the source. In its current formulation, however, the linear sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Moreover, p z = p is typically fixed to be a unit vector (|p| = 1). Note that in their analysis of the TD-LSM for the wave equation [30], the authors argue that one may choose τ z = τ = 0.…”
Section: The Inverse Problem and The Linear Sampling Methodsmentioning
confidence: 99%
“…Moreover, p z = p is typically fixed to be a unit vector (|p| = 1). Note that in their analysis of the TD-LSM for the wave equation [30], the authors argue that one may choose τ z = τ = 0.…”
Section: The Inverse Problem and The Linear Sampling Methodsmentioning
confidence: 99%
“…Of course, this is physically possible only when the prescribed point lies inside the scatterer. It can be shown that the focusing function j is proportional to the inverse of the contrast source function χ [13]. In particular, the inverse of χ exists and is bounded in the L 2 norm only for points zäD (where χ is strictly nonzero).…”
Section: Comparison With the Linear Sampling Methodsmentioning
confidence: 99%
“…The linear sampling method has been interpreted as a focusing technique [13,19]. As we show in this paper, the solution to the ill-posed integral equation in the linear sampling method corresponds to a focusing function, which is a type of distributed source for focusing wave fields in a medium.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations